Assessment of Lignite-Fired Power Plants Impact on Radon Activity Concentrations - Nafezi, Gazmend; Bahtijari, Meleq (International Journal of Computational and Experimental Science and Engineering, 2024)
Radon activity concentrations has been surveyed in dwellings in the vicinity of an open-cast lignite mine and two lignite-fired power plants in the Pristina region, Kosovo. For this purpose solid-state nuclear track detectors CR-39 were exposed in the winter period for three months. Radon activity concentration ranged from 41 Bq m−3 to 327 Bq m−3, and the resulted annual effective doses was, from 0.74 mSv y−1 to 5.83 mSv y−1. The relationships of radon levels with the age of buildings, building material and local geology has been sought and is discussed. The impact of lignite-fired power plants on indoor radon concentration has not been observed.